Hydrogel and scalp/skin conductivities impact dose from tumor treating fields - Lok, Edwin; Liang, Olivia; Haack, Monika; Wong, Eric T. (Frontiers in Bioengineering and Biotechnology, 2025)
PurposeTumor Treating Fields (TTFields) are delivered by transducer arrays applied to scalp or body surface for treatment of multiple malignancies. Dermatologic complications are thought to be related to hydrogel situated between the electrodes and scalp or skin to facilitate electric field penetration. High intensity of TTFields on these surfaces may also be a contributing factor. We explored conductivity changes in the hydrogel and skin to improve TTFields coverage and penetration.MethodsMagnetic resonance imaging datasets from 12 glioblastoma patients and attenuation-corrected positron emission tomography–computed tomography datasets from 3 non-small cell lung and 2 ovarian carcinoma patients were used to segment anatomic structures. Finite element mesh models were generated and solved for distribution of applied electric fields, rate of energy deposition, and current density at the gross tumor volume (GTV) and clinical target volume (CTV). Electric field-volume, specific absorption rate–volume, and current density-volume histograms were generated, by which plan quality metrics were used to evaluate relative differences in field coverage between models at various hydrogel and skin conductivities.ResultsBy varying conductivity of hydrogel, TTFields coverage at GTV or CTV increased up to 0.5 S/m for head and 1.0 S/m for thorax and pelvis models, and no additional increase was observed beyond these saturation points. Although scalp hotspots increased or decreased by +1.5%, −0.1%, and −0.9% in E5%, SAR5%, and CD5%, the skin hotspots increased by as much as +23.5%, +45.7%, and +20.6%, respectively. When altering conductivity of the entire scalp, TTFields coverage peaked near 1 S/m at the GTV or CTV for the head models. TTFields coverage in both the GTV and scalp increased up to 1 S/m for the head models but plateaued thereafter. Contouring under the scalp increased scalp hotspots by +316% in E5% at 1 S/m compared to altering the conductivity of the entire scalp. GTV hotspots decreased by +17% in E5% at 1 S/m.ConclusionTTFields delivery can be modulated by the conductivity of hydrogel and scalp/skin at the transducer-scalp or transducer-skin interface. Optimizing this aspect of TTFields delivery may increase tumor control while minimizing toxicity at the scalp or skin.